5th MyPSA National Pharmacy Competition (NPC) 2025: pharmaceutical phenomenon - Mursalim, Hani Nurain; Abdul Keram, Norshakila; Zamery, Muhammad ‘Izzuddin (Faculty of Pharmacy, 2025)
The Clinical Pharmacy Challenge (CC) stood as the cornerstone event, where future pharmacists demonstrated their mastery in analysing complex patient cases, formulating evidence-based treatment plans, and defending their therapeutic decisions before expert judges. Taylor’s University Team B emerged victorious, with Universiti Kebangsaan Malaysia Team B and AIMST University Team B securing first and second runner-up positions, respectively.